A PC-based software receiver using a novel front-end technology. - Laddomada, M. (IEEE Communications magazine)
Since the software radio concept was introduced, much progress has been made in the past few years in making it a reality. Many software radio based systems have been designed through the development efforts of both commercial and noncommercial organizations. While the term software radio has meant many things, the ultimate goal in software radio has been the realization of an agile radio that can transmit and receive signals at any carrier frequency using any protocol, all of which can be reprogrammed virtually instantaneously. Such a system places great demands on the limits of data converter and processor technologies since it requires real-time disposition of gigasamples of data produced by direct conversion of wireless signals into digital data. From a processing standpoint, the challenge in software radio is to exploit the three basic processor types-fixed architecture processors, FPGAs, and programmable DSPs/RISCs/CISCs-in such a way as to optimize the three-way trade-offs between speed, power dissipation, and programmability. With respect to the latter characteristic, the issues of high-level language interfaces, portability, and reprogramming speed must be considered. This article describes the architecture and operation of a PC-based software radio receiver. The development environment is a real-time PC-based platform that allows testing to be done in a simple manner using the main software functionality of a PC. The front-end of the receiver implemented in hardware represents a novel wideband design (bandwidth of up to 100 MHz centered at a carrier frequency of up to 2 GHz) that functionally converts wireless signals directly into a gigasample digital data stream in the receiver (and vice versa in the transmitter). This direct conversion approach shows the greatest promise in realizing the main goal of software radio